Effect of Different Remediators on the Control of Phosphorus Release from Landscape River Sediments - Kun, Rong (Journal of landscape research, 2017)
In this paper,different chemicals were added to sediments to control phosphorus release from river sediments by means of different dosing methods,thus reducing the concentration of organic pollutants in overlying water.Two remediators,aluminum sulfate and ferric chloride,were respectively added to six groups of experimental samples in three different covering methods,namely injection,mixing and tiling,and a control group was set up.The results showed that at the initially stationary phase of the experiment,the control effect of phosphorus release from sediments of mixing of aluminum sulfate was the most obvious,followed by tiling and injection into the mud;at the finally stationary phase of the experiment,the control effect of phosphorus release from sediments of injection of aluminum sulfate was the most obvious,followed by mixing and tiling.Under the same coverage,the inhibition effect of aluminum sulfate was more obvious than that of ferric chloride.This paper undertook research into the control effect of phosphorus release from sediments to provide a reference point for the control of water eutrophication in the days to come.